الخبرات الصادمة لدى أمهات الأيتام وعلاقتها بالتوافق النفسي والإجتماعي لدى الأم والطفل : دراسة ميدانية للأم والطفل اليتيم في محافظة غزة - جودة، منيرة محمود (الجامعة الإسلامية بغزة - شئون البحث العلمي والدراسات العليا, 2016)
هدفت الدراسة إلى التعرف على علاقة الخبرات الصادمة لأمهات الأيتام بالتوافق النفسي والاجتماعي لدى الأم والطفل, تكونت عينة الدراسة الفعلية من (76) من أمهات الأيتام وأطفالهن الأيتام الذين تتراوح أعمارهم بين (8-17) سنة والمسجلين في وكالة الغوث بعد حرب 2014 مباشرة، وقد تم اختيارهن بطريقة قصدية، وقد استخدمت الباحثة نوعين من المناهج وهما: المنهج الوصفي التحليلي والمنهج النوعي، استخدمت الباحثة مجموعة من الأدوات هما مقياس غزة للخبرات الصادمة لأمهات الأيتام وأطفالهن، ومقياس التوافق النفسي والاجتماعي لأمهات الأيتام وأطفالهن، كما استخدمت المقابلة الفردية مع أمهات الأيتام وأطفالهن، وقد توصلت الدراسة للنتائج الآتية: بلغ الوزن النسبي للخبرات الصادمة لدى أمهات الأيتام في محافظة غزة بعد حرب 2014 (57.9%) في حين بلغ الوزن النسبي للخبرات الصادمة لدى أطفالهن بوزن نسبي بلغ (58.8%)، بلغ الوزن النسبي لمستوى التوافق النفسي والاجتماعي لدى أمهات الأطفال الأيتام بعد حرب 2014 (53.5%)، في حين بلغ الوزن النسبي لمستوى التوافق النفسي والاجتماعي لدى أطفالهن بوزن نسبي (61.1%). كما وأظهرت الدراسة إلى عدم وجود فروق جوهرية ذات دلالة إحصائية في درجات التوافق النفسي والاجتماعي الكلي لدى أمهات الأيتام في محافظة غزة تعزى إلى المتغيرات التالية: (العمر، نوع الاسرة (نووية، ممتدة)، المستوى الاقتصادي، المستوى التعليمي، عدد الأفراد). كما أظهرت الدراسة عدم وجود فروق جوهرية ذات دلالة إحصائية في درجات التوافق النفسي الكلي لدى الأطفال الأيتام في محافظة غزة تعزى إلى المتغيرات التالية )نوع الجنس، المستوى الاقتصادي، عدد أفراد الأسرة).كما وأظهرت النتائج وجود فروق جوهرية ذات دلالة إحصائية في درجات التوافق النفسي والاجتماعي الكلي لدى الأطفال الأيتام في محافظة غزة تعزى (للفئات العمرية، نوع الأسرة (نووية، ممتدة). المستوي التعليمي للأم). The study aims to identify the relationship of the traumatic experiences with the orphans' mothers and their relationship with the psychological and social adjustment for the child and mother. The actual study sample consists of (76) of the orphans' mothers and their children whose age are about (8-17) years and are registered in UNRWA immediately after the war of 2014, and they were selected deliberately. The researcher has used two types of approaches: the descriptive analytical method , The qualitative approach , The researcher has used a number of tools which are: Gaza measure for the traumatic experiences with the orphans' mothers and their children, the measure of the psychological and social adjustment for the orphans' mothers, the measure of the psychological and social adjustment for the orphans. Also she uses individual interviews with the orphans' mothers prepared by the researcher. The study found the following results: The total relative weight of the traumatic experiences of the orphans' mothers in Gaza governorate reached to (57.9%), while the relative weight of the traumatic experiences of their children reached to (58.8%), The relative weight of the level of the psychological and social adjustment of the orphans' mothers after the war of 2014 reached to (53.5%), while the relative weight of the level of the psychological and social adjustment for the orphans after the war of 2014 reached to (61.1%) . There is a lack of significant differences with statistical significance in the degree of the overall psychological and social adjustment for the orphans' mothers in Gaza governorate for (the age groups, the type of family (nuclear, extended), the economic level, the educational levels, the members' numbers of the family), There is a lack of significant differences with statistical significance in the degree of the overall psychological adjustment for the orphans in Gaza governorate due to (the gender , the family's economic level, the members' numbers of the family). There are differences of statistical significance in the degree of the overall psychological and social adjustment in Gaza governorate due to (the age groups ,the type of the family, to the educational level of the mothers).
Keywords: الصحة النفسية -- الرعاية الإجتماعية -- التوافق الإجتماعي -- التوافق النفسي -- الرعاية الإجتماعية -- الأطفال الأيتام -- مستخلصات الأبحاث -- غزة -- فلسطين -- المجتمع الفلسطيني